THE INFLUENCE OF OPERATIONAL RISK, CAPITAL STRUCTURE, AND INTELLLECTUAL CAPITAL ON FIRM PERFORMANCE WITH CORPORATE GOVERNANVE MECHANISMS AS MODERATING VARIABLE - Naibaho, Eduard Ary Binsar; Kurniadi, Timothy Hizkia (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research aims to examine the influence of risk management, capital structure, and intellectual capital on firm performance with corporate governance as moderating variable. In this study, firm performance is measured by Tobin’s Q, operational risk is measured by the natural logarithm of operational loss, capital structure is measured by the DER ratio, intellectual capital is measured by MVAIC, and corporate governance mechanism is measured by board size and board independence. This study uses data from 115 companies located in the ASEAN region which are included in the Consumer Discretionary and Consumer Staples industry categories on S&P Capital IQ during the 2018-2022 period. The sampling method in this research used a purposive sampling method. This study found that operational risk and intellectual capital had no effect on firm performance, while capital structure had a positive impact on firm performance. This research also finds that corporate governance mechanisms can strengthen the positive relationship between operational risk and intellectual capital on firm performance.